Formación de calculos renales de oxalato cálcico en mamíferos - Neira-Carrillo, Andrónico; Vásquez-Quitral, Patricio (Avances en Ciencias Veterinarias, 2010)
Calcium oxalate (CaOx) is the main inorganic component of urolithiasis and is mainly present in the formation of kidney stones in humans. Additionally, oxalocalcic urolithiasis has become the most frequent type of kidney stones, for instance, oxalocalcic urolithiasis has substantially increased in dogs and cats over the last decades. In urolithiasis, urine is supersaturated with calcium and oxalate ions that promote nucleation, growth and aggregation of CaOx crystals. It is accepted that the presence of acidic macromolecules and inorganic compounds in urine is responsible not only for the molecular processes involved in lithiasis but also for the adhesion and endocytosis by renal epithelial cells. Patients with the tendency to form kidney stones may have an alteration in the structure and/or function of some inhibitors of crystallization. In the current review, we describe some general aspects of epidemiology and pathophysiology of oxalocalcic urolithiasis.